Antibiotic prophylaxis for operative vaginal delivery - Liabsuetrakul, Tippawan (Cochrane Database Syst Rev, 2017)
BACKGROUND: Vacuum and forceps assisted vaginal deliveries are reported to increase the incidence of postpartum infections and maternal readmission to hospital compared to spontaneous vaginal delivery. Prophylactic antibiotics may be prescribed to prevent these infections. However, the benefit of antibiotic prophylaxis for operative vaginal deliveries is still unclear. OBJECTIVES: To assess the effectiveness and safety of antibiotic prophylaxis in reducing infectious puerperal morbidities in women undergoing operative vaginal deliveries including vacuum or forceps deliveries, or both. SEARCH METHODS: We searched Cochrane Pregnancy and Childbirth's Trials Register (12 July 2017), ClinicalTrials.gov, the WHO International Clinical Trials Registry Platform (ICTRP) (12 July 2017) and reference lists of retrieved studies. SELECTION CRITERIA: All randomised trials comparing any prophylactic antibiotic regimens with placebo or no treatment in women undergoing vacuum or forceps deliveries were eligible. Participants were all pregnant women without evidence of infections or other indications for antibiotics of any gestational age undergoing vacuum or forceps delivery for any indications. Interventions were any antibiotic prophylaxis (any dosage regimen, any route of administration or at any time during delivery or the puerperium) compared with either placebo or no treatment. DATA COLLECTION AND ANALYSIS: Two review authors assessed trial eligibility and methodological quality. Two review authors extracted the data independently using prepared data extraction forms. Any discrepancies were resolved by discussion and a consensus reached through discussion with all review authors. We assessed methodological quality of the one included trial using the GRADE approach. MAIN RESULTS: One trial, involving 393 women undergoing either vacuum or forceps deliveries, was included. The trial compared the antibiotic intravenous cefotetan after cord clamping compared with no treatment. This trial reported only two out of the nine outcomes specified in this review. Seven women in the group given no antibiotics had endomyometritis and none in prophylactic antibiotic group, the risk reduction was 93% (risk ratio (RR) 0.07; 95% confidence interval (CI) 0.00 to 1.21; low‐quality evidence). There was no difference in the length of hospital stay between the two groups (mean difference (MD) 0.09 days; 95% CI ‐0.23 to 0.41; low‐quality evidence). Overall, the risk of bias was judged to be unclear. The quality of the evidence using GRADE was low for both endometritis and maternal length of stay. AUTHORS' CONCLUSIONS: One small trial was identified reporting only two outcomes. Evidence from this single trial suggests that antibiotic prophylaxis may lead to little or no difference in endometritis or maternal length of stay. There were no data on any other outcomes to evaluate the impact of antibiotic prophylaxis after operative vaginal delivery. Future research on antibiotic prophylaxis for operative vaginal delivery is needed to conclude whether it is useful for reducing postpartum morbidity.